B PENAMBAHAN KALSIUM KARBONAT (CaCO3) DAN MAGNESIUM KLORIDA (MgCl2) TERHADAP STABILISASI DAYA DUKUNG TANAH LEMPUNG - bella agustin; Vivi Septiani; Ahmad Syapawi; Ricky Ravsyan Alhafez (Politeknik Negeri Sriwijaya, 2025)
Soil has high plasticity, expands when air content increases, shrink when conditions are dry. This property causes damage to constructions. So efforts are needed to improve it by increasing the stabilization of the soil itself. In this research, tests were carried out on clay soil originating from the Air Batu area, Banyuasin by adding a variety of mixed materials in the form of Calcium Carbonate (CaCO3) 2%, 4%, 6%, 8%, 10% of the dry weight of the soil and various mixed materials. In the form of optimum Calcium Carbonate (CaCO3) + Magnesium Carbonate (MgCl2) varying from 2%, 4%, 6%, 8%. Testing was carried out in two stages, namely, fascial properties testing which included air content testing, consistency limits, sieve analysis, hydrometer and specific gravity, then mechanical properties testing which included compaction testing, CBR (California Bearing Ratio), the research results showed that the addition of calcium carbonate (CaCO₃) has an effect on stabilizing clay soils. If the percentage of added calcium carbonate (CaCO₃) is greater, the value of the optimum water content will decrease further, while the addition of magnesium chloride (MgCl₂) to the soil is not suitable for stabilizing the soil.